Pengaruh Konsentrasi Susu Skim terhadap Karakteristik Minuman Probiotik Sari Tomat Terfermentasi dengan Isolat Lactobacillus rhamnosus SKG34 - Gita Darmasari, Ni Luh Putu; Nocianitri, Komang Ayu; Duniaji, Agus Selamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p13, 2023)
Tomato is one of the food commodities that have the potential to be developed as probiotic drinks. This research aims to identify the effect of skimmed milk concentration on the characteristics of fermented tomato juice and to identify the proper concentration of skimmed milk in producing fermented tomato juice with the best characteristics. Fermentation of tomato juice used Lactobacillus rhamnosus SKG34 as isolates. The research was designed using Completely Randomized Design (CRD) with concentration of skimmed milk as treatment (0%, 2%, 4%, 6%, 8%, 10%). The data were analyzed by ANOVA and if the treatment affected the variable, then proceed with the Duncan test. The results showed that skimmed milk concentration had a significant effect on total LAB, total acid, pH, hedonic of color and skoring test (color, sour taste and sweet taste). The concentration of 4% skimmed milk produceded the best characteristic of fermented tomato juice with total LAB 1.04 x 10 12 CFU/ml, total sugar 6.02%, total acid 1.49%, pH 4.01, preferred orange color, preferred aroma, preferred sour and slightly sweet taste, and preferred overall acceptance.